Bovine Rotavirus in Diarrhoeic Calves: A Combined RNA PAGE and RT-PCR Approach to Study the Burden on Neonatal Calf Health - Saini, Shubham; Dubal, Zunjar Baburao; Malla, Bilal Ahmad; Rajak, Kaushal Kishor; Dhanze, Himani; Bhilegaonkar, Kiran Narayan (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Diarrhoeal diseases in neonatal calves pose significant health and economic challenges, with rotavirus, particularly group A rotavirus  (RVA), being a major causative agent of calf diarrhoea globally. This study was aimed to determine the prevalence of bovine rotavirus  (BRV) in diarrhoeic calves from dairy farms in and around Bareilly, Uttar Pradesh, India. A total of 116 diarrhoeic faecal samples were  collected from calves and analysed using RNA-PAGE and RT-PCR targeting the VP6 gene. RNA-PAGE identified 5.17% of samples as positive,  while RT-PCR identified 10.34% of samples as positive. The study highlights the presence of BRV as a significant viral causative agent  of calf diarrhoea in the region and underscores the importance of a combined diagnostic approach to enhance its detection accuracy.
Keywords: Neonatal calf diarrhea; Bovine rotavirus (BRV); Prevalence; RNA PAGE; RT-PCR